Learning Evaluation of Islamic Religious Learning in Increasing Learning Motivation - Dewi, Alya Rahmawati; Dartim, Dartim (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2024)
Evaluation can encourage students to study harder encourage teachers to improve and maximize the quality of the learning process, and also encourage education managers to further improve the facilities and quality of student learning. The learning process will be successful when students have the motivation to learn. Therefore, teachers need to foster student learning motivation. The purpose of this study is to describe the evaluation of PAI learning in increasing student learning motivation. This research uses qualitative methods with an approach (field research) through observation, interviews, and documentation studies. As for the results of this study, increasing student motivation through the evaluation of PAI subjects has been seen optimally from the aspects that have been observed.